Speak to the past and it shall teach thee: an appraisal of child health policy in Nigeria. (2018)
Healthcare policies have direct impact on people’s wellbeing. In Nigeria, there is no gainsaying the fact that over the years, different health policies initiated and implemented by government at the local, state and federal levels have had monumental impacts on the nation’s wellbeing and development, but at the same time failed to consider cultural elements in policy making processes.. This paper presents a historical review of Nigeria’s healthcare policies and importance of social and cultural elements in policy making processes. It provides an in-depth insight into the complex relationships between institutions, politics and health policy in Africa’s largest and most ethnically diverse country. It also examines the importance of political regimes, economic approaches, cultural patterns/variations, as well as domestic and international influences on health policy and the physical, social and mental wellbeing of Nigerians.